2012
DOI: 10.1016/j.ejpoleco.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corruption on FDI: A parametric and non-parametric analysis

Abstract: This paper analyses the effect of corruption on Multinational Enterprises' (MNEs) incentives to undertake FDI in a particular country. We contribute to the existing literature by modelling the relationship between corruption and FDI using both parametric and non-parametric methods. We report that the impact of corruption on FDI stock is different for the different quantiles of the FDI stock distribution. This is a characteristic that could not be captured in previous studies which used only parametric methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 33 publications
11
93
2
1
Order By: Relevance
“…Moreover, the long run coefficient of -0.02 indicates that a one unit increase in corruption will lead to a decrease of FDIs in BRIC countries by 1.74% in the long run. This negative relationship between corruption and FDI can be supported by many past literature like, Freckleton et al (2012), Barassi and Zhou (2012), Bayar (2011), Javorcik and Wei (2009), Cuervo-Cazurra (2008) and Hakkal et al (2008). Though, the findings of these studies were significant unlike the results of this research.…”
Section: Research Findingscontrasting
confidence: 57%
See 1 more Smart Citation
“…Moreover, the long run coefficient of -0.02 indicates that a one unit increase in corruption will lead to a decrease of FDIs in BRIC countries by 1.74% in the long run. This negative relationship between corruption and FDI can be supported by many past literature like, Freckleton et al (2012), Barassi and Zhou (2012), Bayar (2011), Javorcik and Wei (2009), Cuervo-Cazurra (2008) and Hakkal et al (2008). Though, the findings of these studies were significant unlike the results of this research.…”
Section: Research Findingscontrasting
confidence: 57%
“…It was argued that corruption adversely affect Swedish multinational companies' choice of their FDI destinations indicating a significant negative relationship between corruption and FDI (Hakkal et al, 2008). In addition, this result has not changed using parametric and non-parametric analysis offering results that are in favour of the "helpinghand" role of corruption (Barassi and Zhou, 2012).…”
Section: Literature Reviewsupporting
confidence: 48%
“…The works of Lui (1985), Wheeler and Mody (1992), Saha (2001), Egger and Winner (2005), Bjorvatn and Soreide (2005), Wu (2006), Tekin-Koru (2006) and Barassi and Zhou (2012) are examples of this line of study.…”
Section: (Ii) Corruption Acting As the "Helping Hand" In Fdimentioning
confidence: 99%
“…4 The cross derivatives of cost functions with respect to mobile skills and the level of corruption are as…”
Section: Assumptionsmentioning
confidence: 99%
“…Poor institutional development and high risk deter foreign investment (Cheung & Qian, 2009 Barassi and Zhou (2012) found that corruption in a country acts like a "grabbing-hand" that increases the cost of doing business and thus discourages FDI inflows. On the other hand, Bjorvatn and Soreide (2005) and Shah (2001) argued that corruption can be a "helping-hand" and become an efficient "lubricant" for rigid regulation and red-tape and thus encourage FDI.…”
Section: The Determinants Of Fdi: Hypothesesmentioning
confidence: 99%